2018
DOI: 10.1101/310961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of novel genes including rpmF and yjjQ critical for Type II persister formation in Escherichia coli

Abstract: 7Persister cells, which are characterized by inactive metabolism and tolerance to antibiotics or 1 8 stresses, pose a significant challenge to the treatment of many persistent infections. Although 1 9 3 1(ydcX), which are two well-known persister genes while the remaining 11 novel genes (gnsA, 3 2 gnsB, ybfA, yjjQ, ymdF, yhdU, csgD, yncN, rpmF, yohJ, rbsD) have not been reported 3 3 previously. Persister levels of 7 constructed knockout mutants (ΔgnsA,Δ ybfA, Δ yjjQ, Δ yhdU, 3 4 Δ csgD, Δ yohJ andΔ rpmF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Meanwhile, we also found while some ribosomal proteins were downregulated, some others were up-regulated in both stationary phase forms (Figure 2, Table 1). In a recent study, rpmF encoding a ribosomal protein was also identified as a persister gene in E. coli [47], which supports the possibility that certain ribosomal proteins may play a role in persister formation or survival in Borrelia SP and MC forms. In future studies we will confirm whether these proteins or genes are involved in persistence to antibiotics and multiple stresses.…”
Section: Discussionmentioning
confidence: 63%
“…Meanwhile, we also found while some ribosomal proteins were downregulated, some others were up-regulated in both stationary phase forms (Figure 2, Table 1). In a recent study, rpmF encoding a ribosomal protein was also identified as a persister gene in E. coli [47], which supports the possibility that certain ribosomal proteins may play a role in persister formation or survival in Borrelia SP and MC forms. In future studies we will confirm whether these proteins or genes are involved in persistence to antibiotics and multiple stresses.…”
Section: Discussionmentioning
confidence: 63%
“…RpmC was previously shown to bind puromycin, an aminonucleoside antibiotic, in both E. coli and Bacillus stearothermophilus 33 . Also, rpmF was previously shown to be involved in membrane lipid synthesis 34 and persister cell formation which may help bacteria to survive antibiotic treatment 35 . RpmF depleted E. coli mutants were shown to increase susceptibility against ampicillin, gentamicin, levofloxacin, metronidazole, rifampicin and sulfamethoxazole in different studies 35 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, rpmF was previously shown to be involved in membrane lipid synthesis 34 and persister cell formation which may help bacteria to survive antibiotic treatment 35 . RpmF depleted E. coli mutants were shown to increase susceptibility against ampicillin, gentamicin, levofloxacin, metronidazole, rifampicin and sulfamethoxazole in different studies 35 37 . RpsU was shown to be related to motility and biofilm formation in Bacillus subtilis 38 , stress resistance in Listeria monocytogenes 39 , metronidazole resistance in Helicobacter pylori 40 , and daptomycin and vancomycin susceptibility in Staphylococcus aureus 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The rpmF gene encodes for the 50S ribosomal subunit protein L32, which is responsible for protein synthesis and membrane lipid synthesis 101 . It is also involved in multidrug tolerance by modulating biofilm formation and persister cell induction 102 .…”
Section: Discussionmentioning
confidence: 99%